Screening of bacteriophages for subsequent treatment of resistant Escherichia coli infections transmitted through poultry - Mobeen ur Rashid; Saeed Ahmed; Javed Muhammad; Muhammad Tariq Navid; Waseem Safdar; Aman Karim; Ijaz Ahmad; Haider Ali; Kashif Abdaal (Brazilian Journal of Microbiology, 2026)

Airborne dust particle-induced lung inflammation in mice alleviated by adipose stem cell-derived conditioned medium - Hazrat Zaman; Madiha Habib; Zobia Safdar; Shafi Zaman; Hafiza Sumbul Yousaf; Muhammad Shahbaz Aslam; Zaigham Abbas (Aerobiologia, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Comprehensive techno-economic assessment of commercial scale pyrolysis and co-pyrolysis plant of textile sludge and low-density polyethylene - Arslan Khan; Daniel Ciolkosz; Muhammad Safdar Ali; Waheed Miran; Imtiaz Ali (Process Safety and Environmental Protection, 2026)

AI and Multi-Omics for Climate-Resilient Remediation of Heavy Metal Soil Toxicity - Isma Gul; Muhammad Adil; Siqi Lu; Safdar Bashir; Heli Lu; Muhammad Daud; Younas Iqbal; Yu Tao (Water, Air, & Soil Pollution, 2026)

Meta-analytic evaluation of pyrethroid impacts on mammalian reproductive outcomes across 62 studies - Afzal Nimra; Mahnoor Usman; Javaireya Khan; Hanan Afzal; Amina Gull; Safdar Sidra; Ali Afzal; Muhammad Babar Khawar (Toxicology and Environmental Health Sciences, 2026)

Ti-MOF anchored polyaniline network on separator: A dual-function strategy for polysulfide immobilization and redox enhancement in Li-S batteries - Abdul Majid Khan; Yasir Shah; Fakhar Zaman; Rashida Yahya; Safdar Abbas; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2026)

Use selenium-doped TiO2 single-wall carbon nanotubes as promoter of biochemical indices in Solanum lycopersicum L. under bacterial wilt stress conditions - Asif Kamal; Akhtar Munir; Khizar Hayat Khan; Ulfat Ara; SK Safdar Hossain; Abdulrazak J. Otaru; Muhammad Tahir Amin; Hayat Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of host suitability and larval instar effects on the reproductive potential of entomopathogenic nematodes against lepidopteran pests - Hina Safdar; Sumaira Maqsood; Salman Ghuffar; Aftab Ahmad; Muhammad Hafeez; Hifza Safdar; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Ibrokhim Ismoilov; Feruza Tukhtaboeva; Nazih Y. Rebouh; et al. (Crop Protection, 2026)

Sodium benzoate induces reproductive toxicity via hormonal disruption, ovarian damage and altering kisspeptin/RFRP-3 expression - Safdar Khan; Mohammad Attaullah; Muhammad Zubair; Muhammad Kashif Khan; Rahmat Ali; Sarwat Jahan (Regulatory Toxicology and Pharmacology, 2026)

Artificial intelligence enabled fouling prediction and effect of adsorbent sources in submerged fluidized bed ceramic membrane reactor for food industry wastewater treatment - Tuba Safdar; Muhammad Iqbal; Aisha Syed; Maqbool Khan; Arshad Hussain; Jeonghwan Kim; Rizwan Ahmad (Environmental Research, 2026)

A comprehensive review of thermal ablation technologies for transdermal drug delivery: mechanisms, commercial products, and future smart systems - Muhammad Murtaza; Salman Ali Khan; Hayat Khan; SK Safdar Hossain (Drug Delivery and Translational Research, 2026)

Assessment of methane (CH4) and its nexus with meteorological variables using cross wavelet analysis over South Asia - Khadija Shakrullah; Salman Tariq; Muhammad Nasar-u-Minallah; Safdar Ali Shirazi; Kashif Mahmood (Theoretical and Applied Climatology, 2026)

Assessing Genetic Variation and Population Connectivity in Wallago attu: A Call for Enhanced Conservation Measures - Taqwa Safdar; Khalid Abbas; Cedric Gondro; Sajid Abdullah; Muhammad Anjum Zia (Biochemical Genetics, 2026)

Molecular and functional insights of β-1,3-glucan-binding protein (β-GBP) in polyphenol-based oxidative stress mitigation in whiteleg shrimp (Penaeus vannamei) - Muhammad Safdar; Safdar Imran; Hafiz Ishfaq Ahmad; Mehmet Ozaslan; Xia Wang; Xiuli Chen (Aquaculture, 2026)

Engineering active sites in binary PrCoO3/Mn2V2O7 heterointerface embedded in phosphorus-doped biochar for boosting pH universal water splitting - Sidra Aslam; Muhammad Safdar; Misbah Mirza; Yasir Abbas; Waseem Abbas; Basharat Ali (Fuel, 2026)

A Novel Homozygous Loss-of-Function Variant in GPR156 Delineates Non-syndromic Hearing Loss - M. Muaaz Aslam; Safdar Abbas; Shoaib Nawaz; Gohar Zaman; Ishtiaq Ahmed; Misbahuddin Rafeeq; Ziaullah M. Sain; Alaa Hamed Habib; Muhammad Umair; Khadim Shah (Biochemical Genetics, 2026)

Genomic and molecular characterization of TGF-beta superfamily in Parus major - Mehwish Sultana; Shakeela Parveen; Muhammad Farhan Khan; Muhammad Tayyab; Muhammad Hussain; Saman Shabir; Warda Safdar; Laiba Shafique (Organisms Diversity & Evolution, 2025)

Understanding the role of Hedgehog signaling pathway and gut dysbiosis in fueling liver cancer - Naz Fatima; Hooriya Fatima; Sadia Ahmad; Muhammad Abu Talha Safdar Hashmi; Nadeem Sheikh (Molecular Biology Reports, 2025)

Cystic fibrosis in Pakistan: population harbouring rare variants non-responsive to CFTR modulators and the dilemma of poor health facilities - Anum Safdar; Muhammad Usman Ghani; Iqbal Bano; Tahir Mehmood; Hassan Rafique; Muhammad Farooq Sabar; Ali Akbar; Rehan Sadiq Shaikh (Molecular Biology Reports, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Improving Soil Fertility, Seed Yield, and Oil Quality of Sunflower Through Application of Processed Animal Manure Under Rainfed Conditions - Ghulam Abbas Shah; Mughees Mustafa; Zheli Ding; Zahid Mahmood; Faheem Khan; Shujaat Hussain Khan; Safdar Ali; Ghulam Mustafa Shah; Imran Mahmood; Muhammad Bilawal Junaid; Munirah Abdullah Al-Dosary; Muhammad Habib Ur Rehman; et al. (International Journal of Plant Production, 2025)

An effective encryption approach using a combination of a non-chain ring and a four-dimensional chaotic map - Muhammad Umair Safdar; Tariq Shah; Asif Ali (Cognitive Neurodynamics, 2025)

Investigating the toxicity risk of fourteen insecticides to a biocontrol agent Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) compared to its prey Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Shoaib Hassan; Muhammad Kamran; Sarfraz Ali Shad; Safdar Khalil (Crop Protection, 2025)

Long-term impacts of agronomic practices on winter wheat yield, water use efficiency, and nitrogen use efficiency in global dryland regions: A meta-analysis - Muhammad Adil; Zhenchuang Wang; Yi Chen; Heli Lu; Siqi Lu; Safdar Bashir; Isma Gul; Huan Li; Zongran Han; Wanfu Feng (Soil and Tillage Research, 2025)

First report of Alternaria alternata causing leaf blotch and fruit spot of apple in Pakistan - Sami Ullah; Samiullah; Naseer Ahmed; Muhammad Kamran; Muhammad Ibrahim; Safdar Ali; Adnan Kashif (New Zealand Journal of Botany, 2025)

Heat stress in riverine buffaloes: regulatory mechanism, physiological changes, production and reproductive performance, and mitigation strategies - Faiz-ul Hassan; Nouman Ashraf; Muhammad Asif Arain; Muhammad Mushahid; Muhammad Safdar; Muhammad Saif-ur-Rehman; Atique Ahmed Behan (International Journal of Biometeorology, 2025)

Do financial inclusion and green growth matter for environmental sustainability? A fresh insight through nonlinear model - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Noreen Safdar; Muhammad Faheem (Clean Technologies and Environmental Policy, 2025)

The role of mentorship in veterinary practice: An empirical study of the Animal Health Mentoring Framework in Pakistan - Ujala Fatima Shan; Aneela Zameer Durrani; Muhammad Zahid Iqbal; Shakera Sadiq Gill; Esha Binte Iqbal; Sadia Sanaullah; Muhammad Aftab; Mahrukh Ahmed; Safdar Aman (The Veterinary Journal, 2025)

Solvothermal synthesis of ruthenium doped MnV2O7@g-C3N4 nanocomposite for oxygen evolution reaction and high-performance asymmetric supercapacitors - Sidra Aslam; Muhammad Safdar; Sadia Akram; Muhammad Awais; Basharat Ali; Yasir Abbas; Waseem Abbas; Misbah Mirza (Journal of Environmental Chemical Engineering, 2025)

Hydropriming and Nano-Priming with Zinc and Iron Oxide Nanoparticles Improved Growth and Physio‑Biochemical Attributes of Sugarcane (Saccharum officinarum L.) Propagated Through Bud Nodes - Rafi Qamar; Syed Nasir Abbas; Atique-ur-Rehman; Hafiz Muhammad Rashad Javeed; Muhammad Ather Nadeem; Muhammad Ehsan Safdar; Muhammad Yaseen; Arkadiusz Artyszak; Mona S. Alwahibi; Manal Abdulaziz Binobead (Journal of Soil Science and Plant Nutrition, 2025)

Conserving the genetic resources of Rita rita: A GIS-mapping based approach - Muhammad Waseem; Khalid Abbas; Taqwa Safdar; Muhammad Sarfraz Ahmed; Noreen Asghar; Zahida Rasheed; Sumra Naz (Fisheries Research, 2025)

Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Muhammad Hamza Shahid; Ghulam Mustafa Sahi; Zunaira Afzal Naveed; Safdar Ali; Muhammad Wahab; Muhammad Sagheer; Azher Mustafa (Journal of Plant Diseases and Protection, 2025)

Regulation of energy metabolism by non-coding RNAs in livestock species: a review - Faiz-ul Hassan; Muhammad Safdar; Muhammad Younus; Muhammad Asif Arain (Journal of Comparative Physiology B, 2025)

Heterojunction interface engineering enabling high transmittance and record efficiency in Sb2S3 semitransparent solar cell - Muhammad Ishaq; Xuerui Li; Safdar Mehmood; Yi-Ming Zhong; Adil Mansoor; Usman Ali Shah; Shuo Chen; Yuexing Chen; Zhuanghao Zheng; Guangxing Liang (Chemical Engineering Journal, 2024)

Characterisation of the essential oil from Iphiona grantioides and investigation of its antibacterial and antioxidant properties - Shah Iram Niaz; Muhammad Ali; Muhammad Saleem; Rubina Qaisrani; Kamran Safdar; Malik Muhammad Akram; Abdur Rauf; Maqbool Ahmad; Sanaullah Abbasi; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2024)

Optimal planning of renewable energy infrastructure for ports under multiple design scenarios considering system constraints and growing transport demand - Linfeng Li; Ming Zhong; Xiaofeng Ma; Haowei Zhao; Muhammad Safdar; Dung David Chuwang; Ziran Zhang (Journal of Cleaner Production, 2024)

Evaluation the Effects of Copper Nanoparticles Dietary Supplementation on Growth Performance, Carcass Characteristics, and Serum Antioxidant Status in Broilers - Bilal Ahmed; Muhammad Sharif; Safdar Hassan; Muhammad Khalid Bashir; Fawwad Ahmad (Biological Trace Element Research, 2024)

Design and Evaluation of Inorganic/Organic Hybrid Bio-composite for Site-Specific Oral Delivery of Darifenacin - Wafa Ishaq; Attia Afzal; Muhammad Farooq; Muhammad Sarfraz; Sherjeel Adnan; Hammad Ahmed; Muhammad Waqas; Zainab Safdar (AAPS PharmSciTech, 2024)
Benign hyperplasia (BHP) is a common disorder that affects men over the age of 60 years. Transurethral resection of the prostate (TURP) is the gold standard for operative treatment, but a range of drugs are also available to improve quality of life and to reduce BHP-associated urinary tract infections and complications. Darifenacin, an anti-muscarinic agent, has been found effective for relieving symptoms of overactive bladder associated with BHP, but the drug has poor solubility and bioavailability, which are major challenges in product development. An inorganic/organic bio-composite with gastric pH-resistant property was synthesized for the targeted oral delivery of Darifenacin to the lower gastrointestinal tract (GIT). This development was accomplished through co-precipitation of calcium carbonate in quince seed-based mucilage. The FTIR, XRD, DSC, and TGA results showed good drug-polymer compatibility, and the SEM images showed calcite formation in the quince hydrogel system. After 72 h, the drug release of 34% and 75% were observed in acidic (0.1N HCl) and 6.8 pH phosphate buffer, respectively. A restricted/less drug was permeated through gastric membrane (21.8%) as compared to permeation through intestinal membrane (65%.) The developed composite showed significant reduction in testosterone-induced prostatic hyperplasia (2.39 ± 0.12***) as compared to untreated diseased animal group. No sign of organ toxicity was observed against all the developed composites. In this study, we developed an inorganic–organic composite system that is highly biocompatible and effective for targeting the lower GIT, thereby avoiding the first-pass metabolism of darifenacin. Graphical Abstract

Review on optimizing dairy sector efficiency: Integrating of genetic markers with managemental techniques - Muhammad Safdar; Muhammad Kaleem; Phelipe Magalhães Duarte; Sina Salajegheh Tazerji; Mehmet Ozaslan; Shahin Hassanpour; Jayadev Rath; Swagatika Priyadarsini; Muhammad Arif Rizwan (Ecological Genetics and Genomics, 2024)

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Eco-friendly approaches for mitigating plastic pollution: advancements and implications for a greener future - Ayesha Safdar; Fatima Ismail; Maryem Safdar; Muhammad Imran (Biodegradation, 2024)

Spatiotemporal investigation of near-surface CH4 and factors influencing CH4 over South, East, and Southeast Asia - Muhammad Athar Khaliq; Farhan Mustafa; Shafeeq Ur Rehman; Muhammad Shahzaman; Zeeshan Javed; Muhammad Sagir; Safdar Bashir; Hongchao Zuo (Science of The Total Environment, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

An assessment of bilateral debt swap financing indispensable for economic growth and environment sustainability: a policy implication for heavily indebted countries - Umar Suffian Ahmad; Sadia Safdar; Muhammad Azam (Environmental Science and Pollution Research, 2023)

Synergized toxicity exhibited by indigenous entomopathogenic fungal strains, plant extracts and synthetic insecticides against fall armyworm Spodoptera frugiperda (J.E. Smith) under laboratory and semi-field conditions - Kanwer Shahzad Ahmed; Muhammad Zeeshan Majeed; Samy Sayed; Bader Z. Albogami; Laila A. Al-Shuraym; Hina Safdar; Ikram Ul Haq; Abu Bakar Muhammad Raza (Journal of Plant Diseases and Protection, 2023)

Effect of Dietary Supplementation of Zinc Nanoparticles Prepared by Different Green Methods on Egg Production, Egg Quality, Bone Mineralization, and Antioxidant Capacity in Caged Layers - Safdar Hassan; Muhammad Sharif; Muhammad Aslam Mirza; Muhammad Saif ur Rehman (Biological Trace Element Research, 2023)

A bacterial consortium and L-tryptophan boosted glyphosate removal, mungbean growth and physiology in contaminated soil - Qammar Farooq; Muhammad Imran Khan; Muhammad Hayder Ali; Safdar Bashir; Muhammad Azam; Rashad Qadri; Basharat Ali; Muhammad Dawood; Muhammad Iftikhar Hussain (Arabian Journal of Geosciences, 2023)

Exploring the role of HaTIPs genes in enhancing drought tolerance in sunflower - Tania Safdar; Muhammad Hammad Nadeem Tahir; Zulfiqar Ali; Muhammad Habib ur Rahman (Molecular Biology Reports, 2023)

I act in an environmentally responsible fashion since my firm is socially responsible: A pathway for transition to a responsible society - Qinghua Fu; Jawad Abbas; Ghadahanfar Bin Alarif; Muhammad Safdar Sial; Talles Vianna Brugni; Nofal Adamwal (Journal of Cleaner Production, 2023)

Digitalized world and carbon footprints: does digitalization really matter for sustainable environment? - Muhammad Zulfiqar; Safdar Husain Tahir; Muhammad Rizwan Ullah; Sadeen Ghafoor (Environmental Science and Pollution Research, 2023)

Seismic Performance of Helical Piles—A State of the Art Literature Review - Hamza Ahmad Qureshi; Muhammad Safdar (Arabian Journal of Geosciences, 2023)

Developing a Novel Methodology by Integrating Deep Learning and HMM for Segmentation of Retinal Blood Vessels in Fundus Images - Mehdi Hassan; Safdar Ali; Jin Young Kim; Ayesha Saadia; Muhammad Sanaullah; Hani Alquhayz; Khushbakht Safdar (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

Bombax ceiba flower extract mediated synthesis of Se nanoparticles for antibacterial activity and urea detection - Muhammad Safdar; Sidra Aslam; Misbah Akram; Adnan Khaliq; Samreen Ahsan; Atif Liaqat; Misbah Mirza; Muhammad Waqas; Waseem Akhtar Qureshi (World Journal of Microbiology and Biotechnology, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Observed and predicted precipitation variability across Pakistan with special focus on winter and pre-monsoon precipitation - Fasiha Safdar; Muhammad Fahim Khokhar; Fatimah Mahmood; Muhammad Zeeshan Ali Khan; Muhammad Arshad (Environmental Science and Pollution Research, 2023)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Development of a constitutive model for fibre reinforced cemented Toyoura sand - Muhammad Safdar; Tim Newson; Faheem Shah (European Journal of Environmental and Civil Engineering, 2022)

Development of Organically Complexed-Bioaugmented Boron-Coated DAP and Its Effect on Yield and Quality of Canola (Brassica napus L.) - Tayyaba Samreen; Muhammad Imran; Zahir Ahmad Zahir; Muhammad Zulqernain Nazir; Saima Noureen; Safdar Bashir; Sehrish Kanwal; Hassan Munir; Muhammad Aamer Maqsood (Journal of Plant Growth Regulation, 2022)

Adrenergic blocker terazosin potentially suppresses acetaminophen induced-acute liver injury in animal models via CYP2E1 gene - Zoya Hashmat; Iffat Saeed Channa; Muhammad Safdar; Mehmet Ozaslan; Muhammad Saeed; Faisal Siddique; Yasmeen Junejo (Toxicological Research, 2022)

Relational pre-impact assessment of conventional housing features and carbon footprint for achieving sustainable built environment - Syed Shujaa Safdar Gardezi; Nasir Shafiq; Muhammad Waris Ali Khan (Environment, Development and Sustainability, 2022)

Correction to: Antioxidant and antibacterial activities of Artemisia absinthium and Citrus paradisi extracts repress viability of aggressive liver cancer cell line - Muhammad Ali; Rida Iqbal; Muhammad Safdar; Sehrish Murtaza; Ghulam Mustafa; Muhammad Sajjad; Shazia Anwer Bukhari; Tayyaba Huma (Molecular Biology Reports, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Cytotoxic and anticancer activity of a novel synthesized tet-AuNPs simultaneously activates p53 and inhibits NF-kB signaling in SKBR3 cell line - Muhammad Safdar; Mehmet Ozaslan; Yasmeen Junejo; Iffat Saeed Channa (Toxicology and Environmental Health Sciences, 2022)

Illuminating Empirical Evidence of Climate Change: Impacts on Rice Production in the Punjab Regions, Pakistan - Sohail Abbas; Shazia Kousar; Safdar Ali Shirazi; Muhammad Yaseen; Yasir Latif (Agricultural Research, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Green bond as a new determinant of sustainable green financing, energy efficiency investment, and economic growth: a global perspective - Yiyi Ning; Jacob Cherian; Muhammad Safdar Sial; Susana Álvarez-Otero; Ubaldo Comite; Malik Zia-Ud-Din (Environmental Science and Pollution Research, 2022)

Does foreign direct investment asymmetrically affect the mitigation of environmental degradation in Malaysia? - Muhammad Faheem; Sadam Hussain; ArsalanTanveer; Noreen Safdar; Muhammad Arshad Anwer (Environmental Science and Pollution Research, 2022)

Photosynthesis research under climate change - Sajad Hussain; Zaid Ulhassan; Marian Brestic; Marek Zivcak; Weijun Zhou; Suleyman I. Allakhverdiev; Xinghong Yang; Muhammad Ehsan Safdar; Wenyu Yang; Weiguo Liu (Photosynthesis Research, 2021)

Antioxidant and antibacterial activities of Artemisia absinthium and Citrus paradisi extracts repress viability of aggressive liver cancer cell line - Muhammad Ali; Rida Iqbal; Muhammad Safdar; Sehrish Murtaza; Ghulam Mustafa; Muhammad Sajjad; Shazia Anwer Bukhari; Tayyaba Huma (Molecular Biology Reports, 2021)

Foliar Spray of Natural and Synthetic Plant Growth Promoters Accelerates Growth and Yield of Cotton by Modulating Photosynthetic Pigments - Muhammad Shaukat; Ashfaq Ahmad; Tasneem Khaliq; Irfan Afzal; Sher Muhammad; Bushra Safdar; Sabir Hussain Shah (International Journal of Plant Production, 2021)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Screening of wheat (Triticum aestivum L.) genotypes for drought tolerance using polyethylene glycol - Muhammad Adnan Bukhari; Adnan Noor Shah; Shah Fahad; Javaid Iqbal; Fahim Nawaz; Abdul Manan; Mohammad Safdar Baloch (Arabian Journal of Geosciences, 2021)

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies - Muhammad Safdar; Muhammad Sajjad Khan; Abdulkarim Yasin Karim; Shwan Ali Omar; Shukur Wasman Smail; Muhammad Saeed; Sana Zaheer; Mazhar Ali; Bilal Ahmad; Muhammad Tasleem; Yasmeen Junejo (Mammalian Genome, 2021)

Impact of economic freedom on air pollution: configuration analysis of Asia-Pacific region - Safdar Husain Tahir; Shazia Kousar; Farhan Ahmed; Muhammad Rizwan Ullah (Environmental Science and Pollution Research, 2021)

Benzilydene and thiourea derivatives as new classes of carbonic anhydrase inhibitors: an in vitro and molecular docking study - Shama Qaiser; Mohammad S. Mubarak; Sajda Ashraf; Muhammad Saleem; Zaheer Ul-Haq; Muhammad Safdar; Abdur Rauf; Tareq Abu-Izneid; Malak I. Qadri; Aneela Maalik (Medicinal Chemistry Research, 2021)

First report of leaf spot of bottle gourd (Lagenaria siceraria) caused by Fusarium equiseti in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Sabin Aslam; Muhammad Amjad Ali; Nasir Ahmad Khan; Yingyan Zhai; Mark L. Gleason (Journal of Plant Pathology, 2021)

Effect of biochar and compost on cadmium bioavailability and its uptake by wheat–rice cropping system irrigated with untreated sewage water: a field study - Muhammad Zia ur Rehman; Maqsooda Waqar; Safdar Bashir; Muhammad Rizwan; Shafaqat Ali; Ahmed Abd El Fattah El Baroudy; Hinnan Khalid; Muhammad Ashar Ayub; Muhammad Usman; Shah Jahan (Arabian Journal of Geosciences, 2021)

The Relevance of SNPs at 3′UTR Region of CASP7 and miR-371b-5p Associated Diseases: A Computational Analysis - Muhammad Safdar; Sana Zaheer; Rozhgar A. Khailany; Sadaf Parvez; Muhammad Naveed; Piplu Bhuiyan; Mehmet Ozaslan; Rebaz Moatasam; Mustafa S. Al-Attar; Musarrat Abbas Khan; Yasmeen Junejo (Cell Biochemistry and Biophysics, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Nano-particles of Trace Minerals in Poultry Nutrition: Potential Applications and Future Prospects - Safdar Hassan; Faiz-ul Hassan; Muhammad Saif-ur Rehman (Biological Trace Element Research, 2020)

Physiological response of spinach to toxic heavy metal stress - Muhammad Zubair; Qudrat Ullah Khan; Nosheen Mirza; Rizwana Sarwar; Asghar Ali Khan; Mohammad Safdar Baloch; Shah Fahad; Adnan Noor Shah (Environmental Science and Pollution Research, 2019)

An Investigation into the Accumulation of Air Borne Trace Metals in the Lungs of Common Myna Acridotheres tristis and Bank Myna Acridotheres ginginianus Captured from Urban and Semi Urban Areas of Lahore and Pattoki, Pakistan - Nida Irshad; Safdar Sidra; Arshad Javid; Sitara Ashraf; Muhammad Rizwan Ullah; Rafia Zafar (Bulletin of Environmental Contamination and Toxicology, 2019)

Molecular genetic analysis of consanguineous families with primary microcephaly identified pathogenic variants in the ASPM gene - MUZAMMIL AHMAD KHAN; CHRISTIAN WINDPASSINGER; MUHAMMAD ZEESHAN ALI; MUHAMMAD ZUBAIR; HADIA GUL; SAFDAR ABBAS; SAADULLAH KHAN; MUHAMMAD BADAR; RAMZI M. MOHAMMAD; ZAFAR NAWAZ (Journal of Genetics, 2017)

Genetic analysis of post-weaning growth traits of Thalli sheep under tropical conditions - Asghar Hussain; Pervez Akhtar; Safdar Ali; Khalid Javed; Muhammad Younas; Abdul Shakoor; Usman Waheed (Tropical Animal Health and Production, 2014)

Upgrade of egg quality through different heat-combating systems during high environmental temperature - Muhammad Safdar Anjum; Mansur Abdullah Sandhu; Nasir Mukhtar; Zia-ur Rahman (Tropical Animal Health and Production, 2014)

Expression patterns of miR-221 and its target Caspase-3 in different cancer cell lines - Sercan Ergun; Kaifee Arman; Ebru Temiz; İbrahim Bozgeyik; Önder Yumrutaş; Muhammad Safdar; Hasan Dağlı; Ahmet Arslan; Serdar Oztuzcu (Molecular Biology Reports, 2014)

Tree species as a potential source of bio-herbicides for controlling Parthenium hysterophorus L. - Muhammad Ehsan Safdar; Asif Tanveer; Abdul Khaliq; Muhammad Shahbaz Naeem; Salman Ahmad (Natural Product Research, 2013)

Organic amendments differ in their effect on microbial biomass and activity and on P pools in alkaline soils - Muhammad Asghar Malik; Khalid Saifullah Khan; Petra Marschner; Safdar Ali (Biology and Fertility of Soils, 2013)

Carnivore diet analysis based on next‐generation sequencing: application to the leopard cat ( Prionailurus bengalensis ) in Pakistan - WASIM SHEHZAD; TIAYYBA RIAZ; MUHAMMAD A. NAWAZ; CHRISTIAN MIQUEL; CAROLE POILLOT; SAFDAR A. SHAH; FRANÇOIS POMPANON; ERIC COISSAC; PIERRE TABERLET (Molecular Ecology, 2012)
Diet analysis is a prerequisite to fully understand the biology of a species and the functioning of ecosystems. For carnivores, traditional diet analyses mostly rely upon the morphological identification of undigested remains in the faeces. Here, we developed a methodology for carnivore diet analyses based on the next‐generation sequencing. We applied this approach to the analysis of the vertebrate component of leopard cat diet in two ecologically distinct regions in northern Pakistan. Despite being a relatively common species with a wide distribution in Asia, little is known about this elusive predator. We analysed a total of 38 leopard cat faeces. After a classical DNA extraction, the DNA extracts were amplified using primers for vertebrates targeting about 100 bp of the mitochondrial 12S rRNA gene, with and without a blocking oligonucleotide specific to the predator sequence. The amplification products were then sequenced on a next‐generation sequencer. We identified a total of 18 prey taxa, including eight mammals, eight birds, one amphibian and one fish. In general, our results confirmed that the leopard cat has a very eclectic diet and feeds mainly on rodents and particularly on the Muridae family. The DNA‐based approach we propose here represents a valuable complement to current conventional methods. It can be applied to other carnivore species with only a slight adjustment relating to the design of the blocking oligonucleotide. It is robust and simple to implement and allows the possibility of very large‐scale analyses.

Developmental and photosynthetic regulation of δ-endotoxin reveals that engineered sugarcane conferring resistance to ‘dead heart’ contains no toxins in cane juice - Muhammad Sarwar Khan; Safdar Ali; Javed Iqbal (Molecular Biology Reports, 2011)

A convenient iodination method for alcohols using cesium iodide/methanesulfonic acid and its comparison using cesium iodide/ p -toluenesulfonic acid or cesium iodide/aluminium chloride - Khalid Mohammed Khan; Shahnaz Perveen; Safdar Hayat; Muhammad Ali; Wolfgang Voelter (Natural Product Research, 2008)

Effect of seedling age and water depth on morphological and physiological aspects of transplanted rice under high temperature - Abdul Aziz Khakwani; Masaaki Shiraishi; Muhammad Zubair; Mohammad Safdar Baloch; Khalid Naveed; Inayatullah Awan (Journal of Zhejiang University-SCIENCE B, 2005)